A educação inclusiva para surdos: uma análise do saber matemático intermediado pelo intérprete de Libras - Borges, Fábio Alexandre (2013)
Concerning the current discourse favorable to the Inclusive Education, ali the students have been invited to share the same space. In the political sphere, some measures have been taken, for instance, the approval of Sign Language Law (BRASIL, 2002), which officializes it as weIl as assures the presence of the Sign Language Interpreters (BRASIL, 2005) at the educational attendance, both for the deaf students. Among the existent barriers which are opposed to good quality teaching to the inclusive deaf students, we feature the speaking as the muin mean of communication and the one that permeates all the methodological strategies avaialable to the teacher into the classroom. Besides, some important aspects have not been considered in view of the real deaf inclusion, as the valorization of those students' visual experiences. In this sense, the current research aims to understand how the Mathematics tiaching and leaming process occurs regarding deaf students who rely on the support of a Sign Language Interpreter. In order to accomplish it, we carried out our research in two groups of students from the 9th (ninth) grade Elernentary Education from different schools, which we name here as Case 1 and Case 2. Taking into account Case 1, we observed 30 (thirty) Mathematics classes in a public school in the north of Paraná. To organize the data, we used field notes to identify the main characteristics that are part of the Mathematics teaching and learning process to inclusive deaf students. Besides the field notes, we applied 12 (tweive) Mathematics activities to the deaf and hearer students from the sarne school, but (he deaf ones were video recorded whiie doing the activities. Considering Case 2, we also observed three Mathematics classes in a public school in the north of Paraná. Ail the classes were audio and video recorded and transcribed, with special attention to the teacher's speech und the Sign Language interpreter's irnages. After that, we compared both the transcriptions to understand the characteristics of the adopted languages, such as the Portuguese and the Sin Language. Both in Case 1 and in Case 2, it was possible to identifi the units of anaiyses drived from the data set: lack of interaction between deaf and hearer students at school; the defluitions of the Sign Language Interpreter's role at school have not been designed yet; lack of activities which explore the visual aspect in the teaching of Mathematics; initial and eontinuing education have not considered the inclusive deaf students; deaf students' dificulties in interpreting the Mathematical statements; and, on the other hand, teachers and other professionals' lack of knowledge about the deaf student's trials with respect to the language that he/she does not know; Mathernatical contradictions made in the translation process to the Sign Language. To sum up, we have proposed some implementations that need to be considered in case of alming a real good quality teaching for everybody, with special attention to the deaf students.